The Pattern of Interpersonal Relationship between Islamic Teachers and Students for Instilling Religious Values in Boarding School System - Ahmad Sholeh; Abd Ghafur; Nurul Yaqien (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This research aims to find out, describe, and find: First, the values that become the foundation of interpersonal relationship of Islamic teachers; Second, the interpersonal relationship models of Islamic teachers for instilling religious values in boarding school system. This research used qualitative research with a multiple case study in MA MAWAR and SMA al-Munawariyah East Java Indonesia. These two institutions were chosen because they have extraordinary developments and have implemented a boarding school system to produce a generation that has akhlaqul Karimah. Data collection techniques used (1) interviews (2) observations and (3) documentation. Data analysis used constant comparative analysis method. Data checking was done in four ways, namely: credibility, transferability, dependability and confirmability. The results showed that the first, the religious teachers make the values of faith and devotion, sincerity, professionalism, process-oriented, openness, integrity, and tawÄdhu` as a foundation in building interpersonal relationships with students. The second, interpersonal relationship model of Islamic teachers in the process of instilling religious values varies greatly. This is in accordance with the characteristics of an Islamic teacher and his educational institution. Some interpersonal relationship models that have been carried out by the Islamic teachers are interactional, humanistic, directive, spiritual religious, authoritative and tolerant. Furthermore, this study also emphasizes the importance of actualizing teacher-student spiritual interpersonal relationships in the learning process so that students' religious attitudes can be achieved in everyday life.